Peserta Didik Berkepribadian Muslim; Implementasi Karakter Berbasis Nilai Pancasila - Wahidah, Emma (STAI Al-Mas'udiyah, 2024)
This research aims to examine the values ​​of Pancasila as the basis of the nation's philosophy and its relevance to the principles of Islamic teachings which are implemented in the Independent Curriculum-based education process which is translated into the Project for Strengthening the Pancasila Student Profile (P-5). The type of research used is library research with a qualitative approach. The aim of conducting a literature study is to find a basis or foundation for obtaining and building a theoretical basis, framework of thinking and determining temporary conjectures or research hypotheses. The results of this research show that basically, educational reconstruction is sought as an alternative solution to educational problems considering that various problem factors will accompany the development of the dynamics of the nation's life. Through the development of P-5, students are directed and given the opportunity to be more able to develop their character and competence more freely according to their needs through knowledge exploration activities, skill development and taking real action. Pancasila which is integrated with the Islamic dimension will form a concept that is more synergistic in order to build higher quality education through the following points: 1) Ketuhanan Yang Maha Esa; Principles of Aqidah and Hablun Minallah, 2) Kemanusiaan yang Adil dan Beradab; Hablun Minannaas, 3) Persatuan Indonesia; Ukhuwah, 4) Kerakyatan yang Dipimpin oleh Hikmat Kebijaksanaan dalam Permusyawaratan Perwakilan; Mudzakarah and Shura, and; 5) Keadilan Sosial bagi Seluruh Rakyat Indonesia; 'Adalah.